Olive and Coffee Cultivation as Sustainable Alternatives in Eastern Indonesia - Maspul, Kurniawan Arif (PT. Altaf Publishing Corp, 2025)
The global clean energy transition, paradoxically, is devastating Eastern Indonesia’s ecological and social fabric. Framed as a geopolitical sacrifice zone for the electric vehicle revolution, the region’s unparalleled biodiversity and 15-billion-tonne carbon sinks are being traded for nickel, leaving Indigenous communities impoverished and ecosystems poisoned. This study posits a radical alternative: a pivot from extractive mining to high-value agroforestry as an act of climate justice and sovereign development. Synthesizing field data, climate modeling, and global case studies, we demonstrate the viability of coffee and olive cultivation in the region’s highlands. Shade-grown coffee agroforestry, proven in Indonesia and Colombia, sequesters carbon at levels rivaling secondary forests while providing sustainable livelihoods. Simultaneously, pioneering microclimate analysis identifies over 92,000 hectares in Eastern Indonesian highlands suitable for olives a perennial crop renowned for its carbon sink capacity and soil stabilization, as evidenced by Spain’s Olivares Vivos project. This agro-ecological model offers a resilient, diversified economy that aligns with the Manokwari Declaration’s conservation goals. We argue this transition is not merely an agricultural shift but a strategic imperative to break the neo-colonial resource curse, advocating for policy support that empowers local communities, secures land tenure, and builds a future where economic prosperity is cultivated from the roots up, not extracted from the ground down.